Yield estimation of coconut in Tumkur district of Karnataka - Basavaraj, G. (Journal of Plantation Crops, 2017)
Coconut in India is cultivated mainly in the states of Kerala, Tamil Nadu, Karnataka and Andhra Pradesh which account for more than 90 per cent of area and production of coconut in the country. With about 10 million people dependent on coconut farming and its allied activities, it contributes to more than 83,000 million rupees to the country’s GDP and about 6 per cent to the edible oil pool. However, there are no precise estimates of its production and productivity. The official statistics on area and production of coconut is being published with two years lag by the Department of Economic and Statistics and hence an assessment of surplus/ deficit production and its repercussion in the coconut market economy could not be made many times. Absence of such statistics at the right time for timely dissemination to stakeholders is considered as an impediment for the development and growth of the industry. Coconut Development Board initiated statistical survey for estimation of production of coconut across major coconut growing states in India by undertaking field surveys and yield estimates based on established phenotypic characters of the buttons/ nuts. The estimation was carried out in Tumkur district of Karnataka also which has the highest area under coconut. A total of 406 farms were surveyed in four taluks of the district covering 4060 bearing palms for productivity estimation. The average number of nuts per palm across all age groups for the district as a whole was 98 nuts. The average productivity for Karnataka which was much below to all India average before 2010-11 saw sudden surge post 2011-12. Questions arise as to what are the underlying factors for such sudden spikes. Across many, data capture, estimation and reporting are critical which go on to determine the decision making process on development and growth of the sector. Decisions are formulated on fixation of prices, trade, planning and execution of welfare schemes and policy making. Hence, scientific estimation initiated by Coconut Development Board on production and productivity augurs well for the sector.